Bio-inspired NoC fault tolerant techniques using guaranteed throughput and best effort services - Sethi, M.A.J. (Elsevier B.V., 2016)
Best Effort (BE) and Guaranteed Throughput services (GT) are the two broad categories of communication services provided in NoC. Few of the existing NoC architectures provide both of these services. GT based services, which are based on circuit switching or connection oriented mechanisms of packet switching, are usually preferred for real time traffic while packet switching services are provided by the BE architecture. In this paper, biologically inspired fault tolerant techniques are implemented on these two different services. Biologically inspired techniques offer novel ways of making NoCs fault tolerant; faults in NoCs arise partly due to advanced nanoscale manufacturing processes and the complex communication requirements of the processing elements (PEs). The proposed NoCs fault-tolerant methods (synaptogenesis and sprouting) are adapted from the biological brain's robust fault tolerant mechanisms. These techniques are implemented on both BE and GT services. From the experimental results, the BE architecture was efficiently utilizing the bandwidth compared to GT services, while throughput utilization of GT services were better. The accepted traffic (flit/cycle/node) of the BE architecture is 6.31 better than GT architecture while the accepted traffic of the bio-inspired techniques is 72.12 better than traditional fault tolerant techniques. Â© 2016 Elsevier B.V. All rights reserved.